2011
DOI: 10.1139/y11-052
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide enhances substance P-induced epithelium-dependent bronchial smooth muscle relaxation in Sprague–Dawley rats

Abstract: Hypocapnia and hypercapnia constrict and relax airway smooth muscle, respectively, through pH- and calcium (Ca(2+))-mediated mechanisms. In this study we explore a potential role for the airway epithelium in these responses to carbon dioxide (CO(2)). Contractile and relaxant responses of isolated rat bronchial rings were measured under hypocapnic, eucapnic, and hypercapnic conditions. Substance P was added to methacholine precontracted bronchial rings with and without epithelium. The role of Ca(2+) was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…They showed that low airway PCO 2 combined with high arterial PCO 2 resulted in a large increase in airway resistance [47]. These findings indicate that CO 2 may have unique properties when delivered through the airways and supports the previously cited in vitro work that airway epithelium plays a part in the relaxant response [22]. Finally the rapidity of the response as seen in the sheep video indicates that neural mechanisms are involved.…”
Section: Resultssupporting
confidence: 64%
See 4 more Smart Citations
“…They showed that low airway PCO 2 combined with high arterial PCO 2 resulted in a large increase in airway resistance [47]. These findings indicate that CO 2 may have unique properties when delivered through the airways and supports the previously cited in vitro work that airway epithelium plays a part in the relaxant response [22]. Finally the rapidity of the response as seen in the sheep video indicates that neural mechanisms are involved.…”
Section: Resultssupporting
confidence: 64%
“…The bronchodilatory effect of CO 2 has been demonstrated in many mammalian species including cats, rats dogs [19,22] as well as sheep and humans However, the literature indicates that it might operate through several distinct mechanisms.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations